High efficiency laser-assisted H^{-} charge exchange for microsecond duration beams - Sarah Cousineau; Abdurahim Rakhman; Martin Kay; Alexander Aleksandrov; Viatcheslav Danilov; Timofey Gorlov; Yun Liu; Cary Long; Alexander Menshov; Michael Plum; Andrei Shishlo; Andrew Webster; et al. (Physical Review Accelerators and Beams, 2017)
Laser-assisted stripping is a novel approach to H^{-} charge exchange that overcomes long-standing limitations associated with the traditional, foil-based method of producing high-intensity, time-structured beams of protons. This paper reports on the first successful demonstration of the laser stripping technique for microsecond duration beams. The experiment represents a factor of 1000 increase in the stripped pulse duration compared with the previous proof-of-principle demonstration. The central theme of the experiment is the implementation of methods to reduce the required average laser power such that high efficiency stripping can be accomplished for microsecond duration beams using conventional laser technology. The experiment was performed on the Spallation Neutron Source 1 GeV H^{-} beam using a 1 MW peak power UV laser and resulted in ∼95% stripping efficiency.